P656 Are trough levels of anti-TNF drugs related with treatment failure and duration of treatment?. (16th January 2018) - Gonzalez-Lopez, J; Llamas, C; Giráldez-Montero, J M; Ferreiro, R; Baston, I; Lamas, M J; Dominguez-Munoz, J E; Barreiro-de Acosta, M
Abstract: Background: Therapeutic drug monitoring of infliximab (IFX) and adalimumab (ADA) in inflammatory bowel disease are commonly used if patients show loss of response, but there are scarce data about the influence of trough levels on prognosis. The aim of the study was to evaluate the relationship between drug concentration of anti-TNF and both treatment failure and duration of treatment in a real-life environment. Methods: A prospective observational study was performed. Patients were included consecutively when visiting the hospital to receive IFX or ADA. Inclusion criteria were adult patients under maintenance treatment with one of the study drugs at standard dose who give consent to participate. In the first visit, blood samples were extracted for drug concentration determination. Patients were followed up for the next 2 years. Trough drug concentrations and drug antibodies were measured by an ELISA technique (Promonitor). Patients with IFX levels <3 µg/ml and ADA <5 µg/ml were considered to be under lower limit of therapeutic range (LLTR). After the follow-up period, the number of patients that continued (success) or discontinued (failures) the treatment was analysed. Any change in dosage (intensification) or in the type of drug was considered to be discontinuation of the treatment. Chi-square test was used to analyse the categorical variables and t-student for the continuous variables with normal distribution. Results: One hundred thirty-four patients were consecutively included, 53 males (40%), 92 (68%) patients with Crohn's disease (CD), and 42 (32%) with ulcerative colitis (UC). Eighty-two (61%) received maintenance treatment with IFX and 52 (39%) with ADA. After finishing the follow-up, 107 (79%) patients continued the same treatment regimen (success). Fifty-nine per cent of this group were with drug concentrations above LLTR. The remaining 27 patients were failures. In the failure group, only 41% of the patients were above LLTR, 18.2% less than in the success treatment group ( p = 0.09). A greater percentage of patients below the LLTR was found in the UC group (41.3% vs. 52.4%, CD and UC respectively ( p = 0.07). Regarding the duration of the treatments, the duration was similar in the group of patients with low concentrations vs. high drug concentrations (46.6 vs. 42.6 months). However, when the duration of treatment was analysed in patients who discontinued, significant differences were observed (43.8 vs. 20.2 months in the LLTR groups respectively). We observed 14 patients with positive antibodies, all of them with drug concentrations below the LLTR. Conclusions: The percentage of patients who continue treatment was higher when drug concentrations were above LLTR. However, these high-levels did not prevent the early relapse in some of them.